Re-inventing care planning in mental health: stakeholder accounts of the imagined implementation of a user/carer involved intervention. Issue 1 (June 2015) - Brooks, Helen; Sanders, Caroline; Lovell, Karina; Fraser, Claire; Rogers, Anne
Abstract Background Despite an increase in mental health innovations designed to increase service user and carer involvement in services, there is evidence that service users and carers are still relatively marginalised. This study aimed to identify key informants operating with knowledge of both policy and practice related to future models of mental health management in order to explore the potential de-implementation of existing care planning and possibilities for the introduction of a training programme designed to implement a new user and carer involved and focussed process of mental health care planning. Methods 13 semi-structured interviews were carried out with key informants from a range of relevant disciplinary backgrounds and professional roles, who were involved locally and nationally in policy, practice and research. The aim of the interviews was to explore their perspectives on contemporary arrangements for care planning procedures and processes and to identify factors that might promote or inhibit the routine incorporation of user/carer led planning. Findings were compared to data derived from service users, carers and professionals to illuminate added value. Results Key stakeholders identified elements of the current care planning context that were likely to impact on the implementability of user - focussed care planning. Like other stakeholders, key informants felt that the proposed intervention coalesced with the increasing normalisation of user involvement as appropriate and desirable. Participants added to existing data by illuminating the need for organisational bureaucracy and the legacy of prior mental health policy and historical practice to be considered in implementation. Adequate relationships within the system were considered by all stakeholders to be crucial to successful implementation and key informants discussed how this could be eroded through attempts at practice standardisation and current connectivity and culture within services. Conclusions The study demonstrated the value of incorporating the perspective of stakeholders not directly involved in service delivery in implementation research designed to inform an intervention at the point of design. Their contribution centred on the identification of factors that appeared not be obvious to those working in the system or emanated from political and policy arenas as well as developing the contextual understanding of themes raised by other stakeholders.